PEMBERDAYAAN MASYARAKAT PESISIR MELALUI SKEMA PEMBIAYAAN KERJASAMA PEMERINTAH DENGAN SWASTA DAN CORPORATE SOCIAL RESPONSIBILITY - Desmiyawati, Desmiyawati; Hasan, H. Amir; Samsir, Samsir; Azlina, Nur (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 10 No 2 (2015))
The main purpose of this study is to conduct analysis, formulations and policy recommendations relating to the implementation of partnership of government and private (KPS) and corporate social responsibility (CSR) in efforts to improve efficiency and optimization of the implementation of both the financing scheme. Research done on coastal villages in two districts in the riau namely Bengkalis and Siak.This research was done through survey and the interview. Data analysis by descriptive quantitatif and qualitative analysis. The survey on the coastal community district Bengkalis shows only a small portion of the community are about 10 percent knew about the CSR. The Results of the survey at the public district Siak only about 12 % those who know the existence of CSR. From exposure people had shared desire / the needs of the local people for CSR is related to the 36 %, cash assistance training in the development of effort by 16 % assistance in form of an opening jobs 12 %. The remaining 36 % of respondents need assistance in form of equipment, scholarship school kids, rural development, aid cash assistance, and scholarship jobs and scholarships, jobs and health-care facilities, jobs and assistance funds, training and scholarships, as well as equipments and money. The results of the interview against one of the leaders of a company that there are around Bengkalis district and Siak district, obtained some information. Regarding the use of the term social responsibility for the community is not familiar because during this term used by the company is community development (CD).
Keywords: CSR, CD, The coastal communities